PEMETAAN KASUS TUBERKULOSIS DI KABUPATEN SAMOSIR TAHUN 2019 – 2020 - Vierto Irennius Girsang; Mercy Grace Simbolon; Elsarika Damanik; Ivan Elisabeth Purba (LPPM STIKES BHAKTI HUSADA BENGKULU, 2023)
Background :Mycobacterium tuberculosis is a bacterium that causes the infectious disease Tuberculosis (TB). As of 3 february 2020, the number of tuberkulosis cases in Indonesia increased from year to year by 526,977 cases with a CNR of 197 / 100.000 population, where in 2018 there were 511,873 cases with a CNR of 193 / 100.000 popuation. The purpose of this study was to determine the spread of tuberculosis cases in Samosir Regency in 2019 and 2020. Methods : The research design used is ecology using secondary data. What can be used is aggregate data with data analysis using the help of Quantum GIS software.Results : The distribution of high cases of tuberculosis by sub-district in Samosir Regency in 2019 has three sub-districts while in 2020 there are two sub-districts. The distribution of high cases of tuberculosis based on population density in Samosir Regency in 2019 was in two sub-districts and in 2020 in three sub-districts.Conclusion : Based on the results of mapping tuberculosis cases in Samosir Regency, it was found that all districts had tuberculosis cases. The distribution of sufferers in the form of red color accumulates in Pangururan District followed by Simanindo District. In terms of population density, the 3 areas with the highest number of red cases are those with a fairly high density, namely Pangururan District, Sitiotio District and Harian District.Keywords :Tuberculosis, Mapping, Samosir.